Persepsi Ibu Pekerja Terhadap Pentingnya Ketersediaan Pojok Laktasi Di Lingkungan Universitas Muhammadiyah Surakarta - Rachmawati, Amelia; , Kusuma Estu Werdani, SKM., M.Kes; , Yuli Kusumawati, S.KM, M.Kes (Epid) (2016)
The problem faced by working mothers on exclusive breastfeeding is increasingly complex, one of which is the availability of lactation facilities in the workplace. Support for working mothers may include the provision of facilities which can be used to breasfeed or express milk. The research objective is to get know in depth the work based on the mother's perception of the availability of internal factor corner of lactation in Universitas Muhammadiyah Surakarta. The design study is a qualitative research with phenomenological approach with two main informants working mothers to breastfeed and 3 informants triangulation. Data were collected through interviews about internal factors include the experience, knowledge, expectations, needs, motivations, emotions, and culture of working mothers on the availability of lactation corner. Interviews showed internal factors affecting the perception of working mothers on lactation facilities available at Universitas Muhammadiyah Surakarta. A facility of corner lactation is very likely to be realized as a form of support for working mothers to continue to provide exclusive breastfeeding.